Role of non-government organizations - Bist, Keshab Bahadur (KVM Research Journal, 2025)
The purpose of this study is to analyze the utility and effectiveness of NGOs to change the economic level of rural people in Nepal. NGOs' major rural development programs in Nepal are agricultural, health and human resource development. The objective of this study is first to analyze the role of NGOs in the sustainable development of agriculture second one is to find out how the NGOs are promoting awareness programs and upgrading infrastructural facilities. For this study, the TROSA project of RUDES Baitadi has been selected, it is supported by OXFAM (Nepal). For a detailed study, relevant information was collected by personal visit, and field survey. The overall analysis of this study reveals that NGOs are playing a very important role to change the living standard of farmers through technical and economic support.